Analisis Hukum Wanprestasi dalam Perjanjian Pinjam Meminjam Uang di Kota Binjai (Studi Pn Binjai No: 61/Pdt.G/2022/PN Binjai) - Lufti Andriansyah Sihaloho; Dianto Gunawan Tamba (Verdict: Journal of Law Science, 2026)
A loan agreement is a form of contractual obligation governed by the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata/KUHPerdata) and plays a significant role in civil legal relationships. In practice, the implementation of such agreements frequently gives rise to disputes due to breaches of contract, particularly when the debtor fails to fulfill the obligations stipulated in the agreement. This study aims to analyze the legal framework governing breaches of contract in loan agreements, examine the forms of civil liability imposed on defaulting debtors, and analyze the legal reasoning adopted by the judges in the Binjai District Court Decision Number 61/Pdt.G/2022/PN Binjai. This research employs a normative juridical method using statutory, case, and conceptual approaches. The research data were obtained through library research encompassing primary, secondary, and tertiary legal materials and were analyzed qualitatively using a deductive method. The findings reveal that the legal regulation of breaches of contract in loan agreements is primarily based on Articles 1238, 1243, 1244, and 1245 of the Indonesian Civil Code, all of whose elements were proven to have been fulfilled in the case under examination. The debtor's civil liability includes the obligation to repay the principal loan, pay the agreed interest, and compensate the creditor for actual losses incurred. Furthermore, the panel of judges rendered a default judgment (verstek) because the defendant failed to appear despite being duly summoned and granted the plaintiff's claims based on valid evidence, including the payment of accumulated interest amounting to IDR 3,816,000,000. This study concludes that the application of breach of contract provisions under the Indonesian Civil Code serves to ensure legal certainty, justice, legal protection, and a balance of rights and obligations between the parties in the implementation of loan agreements.